Moral Spectatorship and Its Discourses: The “Mediapolis” in the Swedish Refugee Crisis - Dahlgren, Peter (Javnost-The Public, 2016)
This presentation seeks to specify key features of the civic response to the unprecedented numbers of refugees who arrived in Sweden during the autumn of 2015, and how civic engagement was mobilized. The discussion underscores the theme of moral spectatorship, using Silverstone’s concept of mediapolis, while the analysis highlights the various contingencies that can shape civic engagement. The empirical starting point is the shifting events and political decisions, along with the rapid evolution of the prevailing- and counter-discourses, that came to impact on the extent and character of Swedish mediated moral witnessing and its practical manifestations. While the major media defined the overall contours of the events, social media were also adding their interpretations (countering as well as supporting the dominant narrative) and providing links to civic practices. After a summary of the socio-political events, I examine the various discursive vectors at play in the situation, both traditional ones that provide a certain starting baseline as well as newer ones that arose in the course the events. I briefly locate these vectors in the context Sweden’s historical self-image and experiences with immigration, highlighting the discursive subject positions offered and pre-dispositions of various groups.